1995
DOI: 10.1093/nar/23.22.4542
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors ATF-1 and CREB-1 bind constitutively to the hypoxia-inducible factor-1 (HIF-1)DNA recognition site

Abstract: The hypoxia-inducible factor-I (HIF-1) was first described as a DNA binding activity that specifically recognizes an 8 bp motif known to be essential for hypoxia-inducible erythropoietin gene transcription.Subsequently HIF-1 activity has also been found in cell lines which do not express erythropoietin, suggesting that HIF-1 is part of a widespread oxygen sensing mechanism. In electrophoretic mobility shift assays HIF-1 DNA binding activity is only detectable in nuclear extracts of cells cultivated in a low ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
160
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(169 citation statements)
references
References 35 publications
6
160
2
1
Order By: Relevance
“…These results extend previous observations that the AP-1 sites of the collagenase and the DTdiaphorase genes are involved in the response to anoxia in carcinoma cell lines of the cervix (HeLa) and the colon (HT29), respectively (Rupec and Baeuerle, 1995;Yao et al, 1994). IL-8 gene activation by anoxia does not appear to be regulated through the HIF-1 transcription complex, unlike the VEGF gene, since no consensus binding site for HIF-1 (Kvietikova et al, 1995) was found in the published IL-8 gene sequence. Binding to the AP-1 consensus sequence found in the VEGF gene is also increased in the response to anoxia in glioma cells (Ryuto et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…These results extend previous observations that the AP-1 sites of the collagenase and the DTdiaphorase genes are involved in the response to anoxia in carcinoma cell lines of the cervix (HeLa) and the colon (HT29), respectively (Rupec and Baeuerle, 1995;Yao et al, 1994). IL-8 gene activation by anoxia does not appear to be regulated through the HIF-1 transcription complex, unlike the VEGF gene, since no consensus binding site for HIF-1 (Kvietikova et al, 1995) was found in the published IL-8 gene sequence. Binding to the AP-1 consensus sequence found in the VEGF gene is also increased in the response to anoxia in glioma cells (Ryuto et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…Nuclear Extract Preparation-Nuclear extracts were prepared as described previously (24). Briefly, 1 ϫ 10 8 cells were washed twice with ice-cold phosphate-buffered saline and once with buffer A (10 mM TrisHCl (pH 7.8), 1.5 mM MgCl 2 , 10 mM KCl).…”
Section: Methodsmentioning
confidence: 99%
“…4. The EPOHBS oligonucleotides have been described previously (24). All oligonucleotides (Microsynth) were purified on 10% polyacrylamide gels prior to 5Ј end-labeling of the sense strand with [␥-32 P]ATP (Hartmann) using T4-polynucleotide kinase (Fermentas).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA binding activity of HIF-1 was determined after Vuori et al (2004), Soitamo et al (2001), Kvietikova et al (1995) as an indicator for hypoxic signalling. Nuclear extraction protocols, developed for rainbow trout (Soitamo et al 2001) were not applicable to small tissue samples.…”
Section: Dna-binding Activity Of the Hypoxia Inducible Factor (Hif-1)mentioning
confidence: 99%
“…Electrophoresis was performed at 150 V, room temperature, 2 h in TBE buffer (89 mM Tris, 89 mM boric acid, 5 mM EDTA). Dried gels were autoradiographed (Kvietikova et al 1995). Calculation of the percentage intensity was based on densitometry of gel images, with the sum of all four bands taken as 100% value.…”
Section: Dna-binding Activity Of the Hypoxia Inducible Factor (Hif-1)mentioning
confidence: 99%